2003
DOI: 10.1021/bi034889i
|View full text |Cite
|
Sign up to set email alerts
|

The Human Islet Amyloid Polypeptide Forms Transient Membrane-Active Prefibrillar Assemblies

Abstract: The formation of amyloid fibrils by the human islet amyloid polypeptide is associated with type II diabetes. While it was previously suggested that the formed fibrils are toxic to pancreatic beta-cells due to membrane permeation activity, more recent studies suggested that protofibrillar assemblies have significantly higher potency in permeating lipid bilayers. Here, we specifically studied the membrane interaction activity of soluble and insoluble islet amyloid polypeptide assemblies at high temporal resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(176 citation statements)
references
References 41 publications
11
162
0
2
Order By: Relevance
“…This increased conductivity was not ion specific, and thus has the potential to depolarize the membrane and lead to cellular dysfunction. A growing body of evidence points to membrane permeabilization by amyloid oligomers as a common mechanism of pathogenesis in amyloid-related degenerative diseases [13,19,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. These studies suggest that membrane permeabilization caused by amyloid oligomers is due to defects in the lipid bilayer, rather than the formation of discrete proteinaceous pores.…”
Section: Cellular Membrane and A␤ Oligomers Toxicitymentioning
confidence: 99%
“…This increased conductivity was not ion specific, and thus has the potential to depolarize the membrane and lead to cellular dysfunction. A growing body of evidence points to membrane permeabilization by amyloid oligomers as a common mechanism of pathogenesis in amyloid-related degenerative diseases [13,19,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. These studies suggest that membrane permeabilization caused by amyloid oligomers is due to defects in the lipid bilayer, rather than the formation of discrete proteinaceous pores.…”
Section: Cellular Membrane and A␤ Oligomers Toxicitymentioning
confidence: 99%
“…Pore formation has been proposed to be a key for membrane disruption (21)(22)(23), but a carpeting, detergent-like mechanism has also been advocated (24,25). There is experimental evidence that intermediates permeabilize membranes (26)(27)(28), whereas other studies implicate fibril growth at the membrane surface (29,30). The structural requirements for membrane activity are also not completely clear.…”
Section: Significancementioning
confidence: 99%
“…However, compared with the study in bulk solution, the study at lipid membrane interface should be more important because hIAPP-induced toxicity in diabetes involves interactions between the cell membrane and misfolded protein. Many studies using phospholipids as model membranes have demonstrated that hIAPP binds strongly to lipid membranes [13][14][15][16][17][18][19], in particular to anionic membranes [18,20]. Moreover, the activity and mechanism of inhibition at membrane interface may be quite different from those in bulk solution.…”
Section: Introductionmentioning
confidence: 99%